Strigolactone promotes photomorphogenesis by B-box protein STH7 in an F-box protein MAX2-dependent manner - Thussagunpanit, Jutiporn; Nakamura, Hidemitsu; Asami, Tadao; Nakano, Takeshi (Agriculture and Natural Resources, 2022)
Photomorphogenesis is the process by which plants respond to light; it involves various signal molecules and phytohormones. This study explored the regulation of the signal transducer STH7, a member of the B-box protein, in photomorphogenesis. Hypocotyl shortening and cotyledon opening after GR24 (a strigolactone analog) and brassinazole (Brz, a brassinosteroid inhibitor) application were observed as photomorphogenesis responses of Arabidopsis. The expression level of the photosynthesis-related genes, ELIP2, CHS, LHCB1 and rbcS, as well as the cell elongation-related genes, SAUR-AC1, TCH4 and PRE1, were analyzed in wild-type Arabidopsis and STH7 mutants. Overexpression of STH7 (STH7ox) upregulated the expression of photosynthesis-related genes. However, the transcription levels of these genes were reduced in the strigolactone signaling mutant (max2) and max2×STH7ox mutants. Treatment with GR24 shortened the hypocotyl in STH7ox. This shortening was reduced in the max2×STH7ox. GR24-treated max2×STH7ox showed a decrease in STH7-downstream genes. The application of Brz reduced hypocotyl elongation and caused cotyledon opening in the STH7ox mutant. However, the functional suppression of STH7 (STH7-SRDX), brassinosteroid gain-of-function (bil1-1D/bzr1-1D), max2, max2×STH7ox and bil1-1D×max2 were weakly sensitive to Brz. Although max2×STH7ox mutants were treated with Brz, upregulations of cell elongation-related genes were observed. The results indicated that MAX2 regulates STH7 which was upregulated by SL, promoting photomorphogenesis in Arabidopsis.